REVIEW OF THEORIES AND MODEL OF RESEARCH ON LIMINALITY IN TOURISM - Farzanna Yashera Abdulla,; Farzanna Yashera Abdulla, (Journal of Islamic, Social, Economics and Development, 2021)
Liminality is important in the tourism field to measure the tourist experience fromtheir satisfaction, whether the actual reality experienced meets their expectations. Conceptualresearch method using the semi-systematic literature review approaches are used in this study.This paper reviews some selected theories and models to comprehend more on the concept ofliminality with tourism. For that, the theories and models that would be examined are FivePhases Tourism Model (1966), SERVQUAL Model (1988), Liminality Tourism StructureModel (2019) and Classical and Post-modern Liminality Comparative Theory (2016). The FivePhases Tourism Model is a model used to describe the experience in various phases:expectation, away trip, tourist destination, return trip, and memories, while SERVQUAL Modelis used to measure the quality of service. The Liminality Tourism Structure Model describesthe tourist experience from various elements such as physical, social, and emotional. Finally,the Classical and Post-modern Liminality Comparative Theory compares the classical liminalexperience of society in ancient times and the liminal experience of post-modern society. Theliterature review results show that the theories and models aid in explaining tourist experienceusing five phases and was influenced by several aspects. Thus, the combination of all theseexisting models related to liminality will help to understand tourists more deeply and measurethe level of tourist satisfaction that are seen from their experience, expectation, and the actualreality being experienced by them.